Radiação solar na regeneração natural de manguezais do nordeste paraense - FERNANDES, Desirée Antéia Jastes (Universidade Federal do Pará, 2019)
This work was done to characterize the weather, the weather configuration of global radiation and radiation balance and evaluate the effects of these variables on the spatial and temporal dynamics of natural regeneration in a mangrove forest in the city of Salinópolis, northeast coast of Para. the work was divided into three chapters that cover: I. Theoretical Foundation; II. Climatology, the radiation balance setting and the influence on the spatiotemporal distribution of the original vegetation of the mangrove forest and; III. The effects of the quantity of solar radiation in the spatiotemporal dynamics of mangrove species in natural and controlled environments. The climate characterization was performed using a series of 32 years of longwave radiation data from NCEP/NOAA. The weather variability of global radiation was obtained with a series of 5-year data, from the microclimatic towers of UFRA and UFPA. The monthly net radiation was determined by empirical methods applied to Wave Swing components Short and Long. In Experimental Site mangrove forest of Cuiarana, Cuiarana Village – Salinópolis, five plots were installed where four were kept under natural conditions and was covered with polyethylene shading (50%), which were determined the floristic composition and horizontal structure through identification, quantification and calculation of phytosociological density and frequency parameters relative and natural regeneration on. The spatio-temporal variability of abundance of species in relation to global radiation was determined by Factorial Principal Component Analysis and Tukey test and Student's t test at 95% confidence. The study was conducted between the months of November/2014 to October/2015 with monthly monitoring of weather and floristic variables. The weather has rainy and less rainy periods which concentrate 45.5% and 54.5% of the annual net radiation, respectively. The weather configuration of global radiation study period revealed to be under the influence of El Niño. The spatiotemporal variability shows that the high intensity of global radiation received, recruited Avicennia germinans individuals positively expressive in natural environments, indicating that environmental faces, provide different degrees of global radiation interception, favoring the photosynthetic processes and promoting warmer temperatures in the soil in the densest areas in vegetation, while Laguncularia racemosa requires less solar radiation than Avicennia germinans, evidenced by the increase in number of individuals in controlled lighting environments, with tolerance to 50% of sunlight retention.